Gout and risk of dementia, Alzheimer's disease or vascular dementia: a meta-epidemiology study - Li, Xuanlin; Huang, Lin; Tang, Yujun; Hu, Xuanming; Wen, Chengping (Frontiers in Aging Neuroscience, 2023)
Abstract Objectives: The association between gout and dementia, Alzheimer's disease (AD) or vascular dementia (VD) is not fully understood. The aim of this meta-analysis was to evaluate the risk of all-cause dementia, AD and VD in gout patients with or without medication. Methods: Data sources were PubMed, Embase, the Cochrane Library, and reference lists of included studies. This meta-analysis included cohort studies assessing whether the risk of all-cause dementia, AD, and VD was associated with gout. Risk of bias was assessed using the Newcastle-Ottawa Quality Assessment Scale (NOS). The Grading of Recommendations Assessment, Development and Evaluation (GRADE) system was used to access the overall certainty of evidence. Risk ratios (RR) with 95% confidence intervals (CI) were pooled using a random-effects model, and publication bias was assessed with funnel plots and egger's test. Results: Six cohort studies involving 2,349,605 individuals were included in this meta-analysis, which were published between 2015 and 2022. The pooling analysis shows that the risk of all-cause dementia was decreased in gout patients [RR = 0.67, 95%CI (0.51,0.89), I2=99%, P= 0.005, very low quality], especially in gout patients with medication [RR = 0.50, 95%CI (0.31, 0.79), I2=93%, P= 0.003, low quality]. The risk of AD [RR = 0.70, 95%CI (0.63, 0.79), I2=57.2%, P= 0.000, very low quality] and VD [RR = 0.68, 95%CI (0.49, 0.95), I2=91.2%, P= 0.025, very low quality] was also decreased in gout patients. Despite the large heterogeneity, the sensitivity analysis indicated that the results were robustness and there was little evidence of publication bias. Conclusions: The risk of all-cause dementia, AD, and VD is decreased in gout patients, but the quality of evidence is generally low. More studies still be needed to validate and explore the mechanisms of this association.